Long‐Term Generation of Longitudinal Spin Order Controlled by Ammonia Ligation Enables Rapid SABRE Hyperpolarized 2D NMR. Issue 12 (1st June 2021) - Vaneeckhaute, Ewoud; De Ridder, Sophie; Tyburn, Jean‐Max; Kempf, James G.; Taulelle, Francis; Martens, Johan A.; Breynaert, Eric
Abstract: Symmetry breaking of parahydrogen using iridium catalysts converts singlet spin order into observable hyperpolarization. In this contribution, iridium catalysts are designed to exhibit asymmetry in their hydrides, regulated by in situ generation of deuterated ammonia governed by ammonium buffers. The concentrations of ammonia (N) and pyridine (P) provide a handle to generate a variety of stereo‐chemically asymmetric N‐heterocyclic carbene iridium complexes, ligating either [3xP], [2xP;N], [P;2xN] or [3xN] in an octahedral SABRE type configuration. The non‐equivalent hydride positions, in correspondence with the ammonium buffer solutions, enables to extend singlet‐triplet or S ⟩ → T 0 ⟩ mixing at high magnetic field and experimentally induce prolonged generation of non‐equilibrium longitudinal two‐spin order. This long‐lasting magnetization can be exploited in hyperpolarized 2D‐OPSY‐COSY experiments providing direct structural information on the catalyst using a single contact with parahydrogen. Separately, field cycling revealed hyperpolarization properties in low‐field conditions. Controlling catalyst stereochemistry by introducing small and deuterated ligands, such as deuterated ammonia, simplifies the spin‐system. This is shown to unify experimental and theoretically derived field‐sweep experiments for four‐spin systems. Abstract : Hydride asymmetry in SABRE catalysts is controlled via in situ generation of deuterated ammonia using three different ammonium buffers. Extended singlet‐triplet mixing provides long‐term generation of longitudinal two‐spin order in hydrides allowing rapid hyperpolarized 2D NMR.